Human herpes virus-7-related severe encephalitis diagnosed using mNGS in immunocompetent pediatric patients - Xin Chen; Huan Zhao; Chunxue Jiang; Tingting Sun; Xuewen Xu; Kai You (Virology Journal)
Abstract Background This study sought to describe the clinical characteristics, examination results, and prognoses of immunocompetent children with human herpes virus 7 (HHV-7)-related severe encephalitis. Methods Twelve immunocompetent children with severe HHV-7-related encephalitis were included, all of whom had HHV-7 DNA ( +) detected in the cerebrospinal fluid via metagenomic next-generation sequencing (mNGS) and were followed up for > 6 months. Results The cohort comprised 75% males, with a median age of 4.5 years; all patients presented with fever and altered consciousness and required PICU admission for severe neurological symptoms. Two patients developed encephalitis sequelae and epilepsy. Abnormal electroencephalography and brain magnetic resonance imaging findings were observed in 90.9% (10/11) and 72.7% (8/11) of the patients, respectively. Five patients required ventilator support due to central respiratory failure (four invasive and one noninvasive). One patient underwent plasma exchange, while another received continuous renal replacement therapy. All patients were treated with acyclovir and immunomodulatory therapy. Four patients had poor prognoses, including one 9-year-old male who died and one 9-year-old female who was diagnosed with febrile infection-related epilepsy syndrome and remained in a coma with a Modified Rankin Scale score of 5 at the 6-month follow-up. Conclusions Older immunocompetent children with severe HHV-7-related encephalitis have poor prognosis and low survival rates, both of which may be improved via empiric acyclovir administration combined with immunosuppressive therapy.